Origin and tectonic implications of the ∼200 Ma, collision-related Jerai pluton of the Western Granite Belt, Peninsular Malaysia. (1st September 2016) - Jamil, Azmiah; Ghani, Azman A.; Zaw, Khin; Osman, Syamir; Quek, Long Xiang
Highlights: A detail Field and Geochemical studies of the Jerai granite. All three components of the Jerai granites show overlapping ages. U-Pb zircon geochronology ∼200 Ma indicates that the granite is part of the Permo Triassic granite. The Jerai magmatism is among the late magmatic events of the Main Range granite, Peninsular Malaysia. Abstract: Triassic granitoids (∼200–225 Ma) are widespread in the Western Belt of Peninsular Malaysia. The Main Range granite is the biggest batholith in the Western Belt composed of peraluminous to metaluminous granite and granodiorite and displays typical ilmenite-series characteristics. Jerai granitic pluton occurs at the northwestern part of the Main Range granite batholith. The Jerai granite can be divided into three facies: (i) biotite-muscovite granite; (ii) tourmaline granite; and (iii) pegmatite and aplopegmatite. Biotite-muscovite granite accounts for 90% of the Jerai pluton, and the rest is tourmaline granite. Geochemical data reveal that pegmatite and tourmaline granite are more differentiated than biotite-muscovite granite. Both pegmatite and tourmaline granite have a higher SiO2 content (70.95–83.94% versus 69.45–73.35%) and a more pronounced peraluminous character. The U–Pb zircon geochronology of the Jerai granite gave an age ranging from 204 ± 4.3 Ma, 205 ± 4 Ma and 205 ± 2 Ma for pegmatite biotite-muscovite granite and tourmaline granite, respectively. The biotite-muscovite Jerai granites are similar to S-type Main Range granite, but the tourmaline granite has a signature of late-stage hydrothermal fluid interaction such as tourmaline quartz pods, the accumulation of large pegmatitic K-feldspar, pronounced peraluminous character, higher SiO2 content. Age evidence of these two granitic facies suggest that they are from the same magma.